2020
DOI: 10.1080/13698575.2020.1796929
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of psychosocial risks for gambling and problem gambling in the Nordic countries

Abstract: Gambling is a relatively common activity in the Nordic countries, while the incidence and prevalence of problem gambling is relatively stable in this context. Social networks and relationships (e.g., gambling activities among family members and peers) have been put forward as relevant factors to consider when monitoring the epidemiological pathways in regard to gambling and problem gambling. The research on gambling and functional or qualitative aspect of networks and relationships (here labelled psychosocial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The study has deepened our knowledge of the psychosocial factors related to PG among Italian seniors and highlights the need for a greater attention to the elderly in gambling research and preventive interventions. Particularly, the findings support and strengthen the view that prevention should not concentrate exclusively on risk and protective factors for the individual, but also address the interpersonal and social level (Nordmyr & Forsman, 2020). As observed, poor relations and well-being were found to be significant risk factors for PG within our Italian sample; previous crossnational studies showed Italians elders score a lower median level of life satisfaction than did participants from other countries (Fagerström et al, 2007) and higher score on the loneliness rate associated to poor health and economic deprivation (Fokkema et al, 2012).…”
Section: Implications For Prevention Strategiessupporting
confidence: 70%
See 2 more Smart Citations
“…The study has deepened our knowledge of the psychosocial factors related to PG among Italian seniors and highlights the need for a greater attention to the elderly in gambling research and preventive interventions. Particularly, the findings support and strengthen the view that prevention should not concentrate exclusively on risk and protective factors for the individual, but also address the interpersonal and social level (Nordmyr & Forsman, 2020). As observed, poor relations and well-being were found to be significant risk factors for PG within our Italian sample; previous crossnational studies showed Italians elders score a lower median level of life satisfaction than did participants from other countries (Fagerström et al, 2007) and higher score on the loneliness rate associated to poor health and economic deprivation (Fokkema et al, 2012).…”
Section: Implications For Prevention Strategiessupporting
confidence: 70%
“…Psychosocial problems can also be recognized as the result of problems related to gambling, according to the idea that disruption of significant relationships is a frequent form of harm characterizing PG (Langham et al, 2015). Psychosocial problems can also have a mediating/moderating effect on the links between various factors and PG by functioning as resiliency factors and in influencing coping (Nordmyr & Forsman, 2020): for instance, few scholars have suggested that the lack of social support and social loneliness may work as vulnerable terrain for anxiety and depression, as well recognized risk factors for gambling (Brooks, 2000;Raylu & Oei, 2004, Wood & Griffiths, 2007. In the absence of a support network, people may see gambling as a way to escape from difficulties related to their unpleasant emotions (Gupta et al, 2004;Wood & Griffiths, 2007), as already observed in studies concerning other kinds of addictions (Holahan et al, 2001;Venuleo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support from meaningful others is generally recognized as an asset that protects us from many risks and harms (Cohen & Wills, 1985 ; Kaakinen et al, 2018 ; Minkkinen et al, 2016 ). However, studies have yielded mixed results regarding the role of social support in gambling and problem gambling (Nordmyr & Forsman, 2020 ). A study by Savolainen et al, ( 2019 ) emphasized the role of offline support, showing that while offline support seems to protect from problem gambling, online support is a risk for problem gambling.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…This finding is contrary to expectations but similar with few studies. A systematic review on psychosocial risks for gambling and problem gambling in Nordic countries, Nordmyr and Forsman ( 57 ) indicate that if social support could be a protective factor of problematic gambling but not in all studies but in two studies, social support is not associated with problematic gambling to young people ( 12 , 58 )].…”
Section: Discussionmentioning
confidence: 99%